STUDI KASUS: PENERAPAN PIJAT OKSITOSIN UNTUK MENGATASI KETERLAMBATAN ONSET LAKTASI PADA PERIODE AWAL POSTPARTUM - Fasiha Fasiha; Nur Umi Sahrani (Jurnal Kebidanan, 2022)
Failure in the breastfeeding process is often caused by the emergence of several problems, both problems for the mother and the baby. Problems from mothers that arise during breastfeeding can start before delivery (antenatal period), in the early postpartum period, and after late labor. Problems with breastfeeding can also be caused by special circumstances, such as delayed onset of lactation on early postpartum period, the mother complaining that her baby often cries or refuses to breastfeed, which then means that the milk is not enough or not good enough to make the decision to stop breastfeeding. Anxiety caused by fear of not being able to produce milk and not having enough milk is the most common reason women fail to start breastfeeding, stop breastfeeding too soon, or start complementary feeding before it is needed. One alternative to help facilitate breast milk is to do oxytocin massage. In this case study, after full breast oxytocin massage before breastfeeding, the milk output was good, the baby showed a good sucking and swallowing response, after the oxytocin massage technique was carried out independently and assisted by the husband, the milk came out smoothly. Mother says that the baby is calm and sleeps soundly not fussy.